DESKRIPSI KETERAMPILAN PROSES SAINS MAHASISWA CALON GURU FISIKA - Hamdani, Hamdani (Jurnal Pendidikan Matematika dan IPA, 2017)
This research was conducted to reveal the science process skills of pre-service physics teacher. There were 241 students (64 men and 177 women) were given the science process skills test. Overall average science process skills score of students at 48.88 with a low category. There are seven aspects of the science process skills were revealed. The average score of predicting 41.55; classifying 41.76; interpreting data 49.37; hypothesize 49.48; plan experiments 50.26; observing 50.34 and apply concepts 59.43. Science process skills of male did not differ significantly with female (sig. 0.717> 0.05). The physic education courses need to improve science process skills of students. Keywords: science process skills, gender